ISLAMIC EDUCATION’S IMPACT ON CULTIVATING ANTI-CORRUPTION VALUES - Yusof, Ahmad Syafiq; Ajmain @ Jima’ain, Muhammad Talhah; Harun, Muhammad Safwan; Wan Ibrisam Fikry, Wan Abdul Rahman; Mohamad Tahir, Zahin (Journal of Human Capital Development (JHCD), 2022)
ABSTRACT Education plays a significant part in developing a person’s personality and teaching ideals. Individuals shall be instilled with good ideals through Islamic education. Surprisingly, education that begins in school has a longer and more lasting effect. Unfortunately, many recent cases now report on issues of integrity that affect people from all walks of life. This is a clear indicator that the value of integrity is seen to be getting thinner among Malaysians. As a result, the research was conducted to assess the impact of Islamic education in instilling the concept of integrity in all communities, including individuals, society, and the country. This is a qualitative study that makes use of library and documentation resources. The study discovered that teachers play a significant role in Islamic education, and that teaching content is critical in creating a positive influence and raising student understanding of the principle of integrity. Al-Quran and Sunnah related to corruption and integrity disclosed in the syllabus of Islamic Education are regarded to be able to offer students a solid understanding as well as assist in the development of a good society in this scenario. Kata kunci: Education, Islam, corruption, integrity, syllabus